2010
DOI: 10.2214/ajr.09.2842
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma Shrinkage After MRI-Guided Focused Ultrasound Treatment: Report of 80 Patients

Abstract: MRI-guided focused ultrasound therapy for leiomyoma can result in nonperfused volume ratio and shrinkage that exceed those in previous clinical trials because the treatment guidelines have been relaxed to allow a greater amount of tissue ablation. The results suggest that a larger nonperfused volume ratio can be achieved, resulting in greater shrinkage and improved relief of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 28 publications
5
96
0
2
Order By: Relevance
“…Both interventional methods have a very short recovery time compared to surgery. The achieved reduction of the myoma volume of 45.8 % after 6 months is in agreement with previous studies with reduction rates of 13.5 -46 % [17,23,24]. Different reasons for the increase in volume reduction beyond the NPV are being dis- cussed.…”
Section: Discussionsupporting
confidence: 91%
“…Both interventional methods have a very short recovery time compared to surgery. The achieved reduction of the myoma volume of 45.8 % after 6 months is in agreement with previous studies with reduction rates of 13.5 -46 % [17,23,24]. Different reasons for the increase in volume reduction beyond the NPV are being dis- cussed.…”
Section: Discussionsupporting
confidence: 91%
“…Reaching high NPVs is the mainstay predictor of therapeutical success in the MR-HIFU treatment of UFs. [21][22][23][24] Another nonthermal tissue damaging effect of HIFU is caused by acoustic cavitation. This mechanical process occurs at high acoustic intensities and leads to the vaporization of tissue water and the formation of rapidly expanding microbubbles, which subsequently collapse with the release of shock waves and high-speed liquid jets, leading to tearing forces, which are followed by direct tissue damage.…”
Section: Hifu -Application Methods and Physical Mechanisms Of Tissue mentioning
confidence: 99%
“…[25][26][27][28] Thus, according to the recent US Food and Drug Administration safety criteria, safety margins of 1.5 cm between the treated UF volume and the adjacent peritoneal serosa have to be considered. 24 …”
Section: Hifu -Application Methods and Physical Mechanisms Of Tissue mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (2,5,6) demonstrated that these results may have been due to the reduced non-perfused volume (NPV) observed immediately after HIFU. The extent of the NPV inside the uterine fibroids has been observed using enhanced magnetic resonance imaging (MRI) following treatment, as an indication of treatment outcome.…”
Section: Introductionmentioning
confidence: 99%